Ethanolic Sisyrinchium palmifolium L. Extract as Natural Preservative for Indonesian Tofu Preparation - Damayanti, Sophi; Maharani, Vanya; Singgih, Marlia; Permana, Benny; Mahardhika, Andhika B; Rizaldi, Defri; Hartati, Rika; Wibowo, Indra (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2022)
Tofu is a food product that is easily contaminated by microbial due to its water content. Some bacteria that usually grow in tofu are Escherichia coli, Bacillus cereus, or Staphylococcus aureus. Preservatives are added to solve the common storage problem. However, some manufacturers use hazardous substances, such as formalin or other chemical substances, as a preservative. Tiwai onion (Sisyrinchium palmifolium L.) is a plant that grows in Borneo and has a broad range of antibacterial activity. This study aimed to examine the activity and effectiveness of Sisyrinchium palmifolium extract as a preservative in tofu. Sisyrinchium palmifolium was extracted using the maceration method with ethanol three times. The concentrated ethanol extract has a 5% water content and was used for the next step. According to the Clinical and Laboratory Standard Institute (CLSI method), the test was done with agar diffusion and broth microdilution methods. The test solution was diluted using DMSO 5% as the solvent, and tetracycline HCl solution as a positive control was diluted using NaCl 0.9%. Agar diffusion method was done with Sisyrinchium palmifolium ethanol extract 10000 Î¼g/mL and tetracycline HCl 50 Î¼g/mL. The microdilution method was done with Sisyrinchium palmifolium ethanol extract with an initial concentration of 40000 Î¼g/mL and tetracycline HCl 2000 Î¼g/mL. The results showed that Sisyrinchium palmifolium ethanolic extract has antibacterial activity with the minimum inhibitory concentration value of 5000 Î¼g / mL. Then, the effectivity of concentrated ethanol extract of Sisyrinchium palmifolium as a preservative in tofu was tested by determining Total Plate Count at an incubation temperature of 37, 25, and 4 Â°C in comparison to potassium sorbate as control. Furthermore, organoleptic evaluation was observed at 25 and 4 Â°C. The results showed that Sisyrinchium palmifolium ethanolic extract was effective as an alternative preservative for tofu at a concentration of 5000 Î¼g/mL. In conclusion, ethanolic extract of Sisyrinchium palmifolium could serve as a novel candidate and effective preservative in tofu.